2021
DOI: 10.1371/journal.pone.0251135
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin ameliorates symptoms of diabetes and renal tubular dysfunction in a rat model of diabetes with enlarged kidney (DEK)

Abstract: Background Sodium-glucose cotransporter 2 (SGLT2) inhibitors are widely used to reduce hyperglycemia. The present study investigated the effects of a SGLT2 inhibitor, empagliflozin, on hyperglycemia in a novel rat model of non-obesity type 2 diabetes with enlarged kidney (DEK). Methods Male DEK rats with non-fasting blood glucose concentrations ≤300 mg/dl and >300 mg/dl were classified as nondiabetic and diabetic, respectively. Groups of nondiabetic (control) and diabetic (DM-cont) rats were fed standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…We found that body weight gain was inhibited in Sham operated rats, as shown in non-treated DEK-DM rats [17,22]. In contrast, body weight gradually increased with age in 1/2Nx rats, with body weight after 21 days being significantly higher in 1/2Nx than in Sham operated rats (Figure 4a).…”
Section: Effect Of Uninephrectomy (1/2nx) On General Conditions Related To Diabetesmentioning
confidence: 58%
See 4 more Smart Citations
“…We found that body weight gain was inhibited in Sham operated rats, as shown in non-treated DEK-DM rats [17,22]. In contrast, body weight gradually increased with age in 1/2Nx rats, with body weight after 21 days being significantly higher in 1/2Nx than in Sham operated rats (Figure 4a).…”
Section: Effect Of Uninephrectomy (1/2nx) On General Conditions Related To Diabetesmentioning
confidence: 58%
“…Since blood glucose concentrations in these 1/2Nx rats were almost normal, hyperglycemia was not considered a major cause of renal enlargement. Similarly, our previous study revealed that the normalization of blood glucose level by the administration of empagliflozin did not prevent renal enlargement in DEK-DM rats [22]. Therefore, the intrinsic growth ability of these kidneys may be enhanced by 1/2Nx.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations